A cellular model for aromatic L-amino acid decarboxylase deficiency and neurotransmitter analysis of available therapeutics using a neuroblastoma cell culture - Khalid, Melati (2015)
Aromatic L-amino acid decarboxylase (AADC) deficiency is a rare pediatric neurotransmitter disease. It is an autosomal recessive genetic disorder affecting to date, less than 100 children worldwide. AADC is the key enzyme required for the synthesis of neurotransmitters in the catecholaminergic and serotonergic pathways. Various mutations at position 11 on the short arm of chromosome 7 are responsible for this condition. To date, no apparent correlation can be identified to link mutations with disease outcome. Disease severity can span the spectrum from mild to complete global disability. Generally, affected children fail to achieve any developmental milestones. Movement disorder resulting from dopamine and serotonin deficiency produces characteristic dystonia and oculogyric crises that occur at regular intervals every 3 to 8 days, each episode lasting on average 6 hours. Autonomic dysregulation in the form of temperature instability and susceptibility to metabolic crisis involving sudden dramatic, life-threatening blood glucose level drop and breathing depression are also hallmarks of AADC deficiency. Current treatment intervention involves bolstering endogenous dopamine levels using MAO inhibitors with concurrent administration of dopamine agonists. Various SSRI are also used to maintain endogenous serotonin levels. Anti-cholinergic agents are also used with various outcomes. More recently, the AADC enzyme co-factor PLP and folinate supplementation has shown some promise in improving general disease outcome. However, the overall response to treatment has been dismal. Due to its rare nature, basic research into the disease is scant. Therapeutic tactics has been dependent on the Parkinson's approach as both conditions share a dopamine deficiency. However, the dopamine deficiency of Parkinson's is due to nigrostriatal dopaminergic neuron death with a late onset while children with AADC deficiency survive entirely without developmental influences from the neurotransmitter. This key difference is believed to be the reason for poor dopamine transmission in AADC deficiency using anti-Parkinson's drugs. This study sought to create a cell model of AADC deficiency to quantify the dopamine synthesis potential of several such drugs. Building on the success of a working cell model, this study also then tried to identify competitive amino acid inhibitors of dopamine. Treatment of SH-SY5Y cells with L-DOPA coaxed dopamine production to levels detectable by HPLC. Subsequent administration of the AADC inhibitor benserazide quelled this effect. Previous efforts to transform immature neuroblastoma cells to a dopaminergic phenotype using all-trans-retinoic acid failed. No detectable level of dopamine was seen via HPLC. Using this model of L-DOPA with concomitant benserazide inhibition to model AADC deficient states, Parnate, bromocriptine, Artane and PLP were tested for their dopamine enhancing capabilities. Parnate, bromocriptine and Artane all produced detectable levels of dopamine but did so only minimally and after a long incubation time. PLP did not induce any dopamine synthesis. This suggests that Parnate, bromocriptine and Artane promotes some dopamine synthesis in this model of AADC deficiency. This mirrors the small gains accorded from their use in AADC deficiency treatment. Unfortunately it also reflects their ineffectiveness. Tryptophan, phenylalanine and tyramine were tested for competitive inhibition of dopamine. Serotonin, its precursor 5-HTP and the catecholamine noradrenaline were also tested for this possible action. 5-HTP was the only one found to inhibit dopamine production. The findings of this study are hoped to fuel research interest into a condition with minimal monetary gains potential. Most importantly, it is hoped to improve treatment outcome and quality of life for AADC deficiency sufferers towards an ultimate cure.